Organelle Genome Inheritance in Deparia Ferns (Athyriaceae, Aspleniineae, Polypodiales) - Kuo, Li-Yaung; Tang, Te-Yen; Li, Fay-Wei; Su, Huei-Jiun; Chiou, Wen-Liang; Huang, Yao-Moan; Wang, Chun-Neng (Frontiers in Plant Science, 2018)
Organelle genomes of land plants are predominately inherited maternally but in some cases can also be transmitted paternally or biparentally. Compared to seed plants (> 83% genera of angiosperm and > 12% genera of gymnosperms), plastid genome (plastome) inheritance has only been investigated in fewer than 2% of fern genera, and mitochondrial genome (mitogenome) from only one fern genus. We developed a new and efficient method to examine plastome and mitogenome inheritance in a fern species—Deparia lancea (Athyriaceae, Aspleniineae, Polypodiales), and found that plastid and mitochondrial DNAs were transmitted from only maternal parentage to a next generation. To further examine whether both organelle genomes have the same manner of inheritance in other Deparia ferns, we sequenced both plastid and mitochondrial DNA regions of inter-species hybrids, and performed phylogenetic analyses to identify the origins of organellar DNA. Evidence from our experiments and phylogenetic analyses support that both organelle genomes in Deparia are uniparentally and maternally inherited. Most importantly, our study provides the first report of mitogenome inheritance in eupolypod ferns, and the second one among all ferns.